An investigation of the support offered by the institution level support team to the foundation phase teachers in a single school in Johannesburg. - Tebid, Celyne Ambeck (My University, 2010)
Some of the major difficulties encountered in embracing an inclusive education system are, lack of commitment, lack of resources as well as a poor understanding of how to support successful inclusion. The Education White Paper 6 (here after referred to as EWP6) states that, all children can learn, should be supported to learn and assured of equal and equitable education. The implementation of inclusion has been initiated by the EWP 6 (Department of Education, 2001) and is still in the process of developing the necessary education support services. At the school level, an institution level support team (ILST) should serve as a means of supporting learners experiencing learning difficulties. This study examined the perceptions of foundation phase teachers regarding the support they are getting from the ILST as well as finding out whether collaboration between the above mentioned bodies can help in addressing the issue of learner diversity in an inclusive classroom. The investigation was conducted at a school in the Northern suburb of Johannesburg. The foundation phase teachers and some members of the ILST were purposively included as participants. A case study design was chosen since this would allow for in-depth examination of the perceptions of foundation phase teachers regarding the support they are getting from their (ILST). The data collection process included questionnaires, oral follow up interviews, document analysis and observation. The data collected from the above sources has been analyzed according to themes and subthemes that emerged. The findings of the study show that, there is little or no collaboration between the foundation phase teachers and the ILST. It was also evident that the foundation phase teachers collaborate immensely amongst themselves in sharing ideas on how to support learners in their classrooms. Lastly, it was apparent that the support given to the foundation phase teachers was done solely by the learning support educator and not as a team with the other members of the ILST. The ILST on their part did not take time to actually define their roles in terms of how they would be functioning in rendering support to the foundation phase teachers. Based on the findings in this study, recommendations are made as to how to effectively support teachers as well as improve collaboration among all stake holders involved in inclusive practices.
Keywords: Inclusive education; Collaboration; Institution Level Support Team; District based Support Team; Diversity; Barriers to Learning, Development and Participation; Learners with Special Educational Needs